Efficacy and Safety of HAPC in Barrett's Esophagus – A Multicenter Italian Prospective Study - Davide Massimi; Roberta Maselli; Silvia Pecere; Cristiano Spada; Gianluca Andrisani; Francesco Maria Di Matteo; Antonella La Terra; Franco Coppola; Antonio Capogreco; Roberto De Sire; Ludovico Alfarone; Maddalena Menini; et al. (Endoscopy International Open)
Background and study aims. Hybrid argon plasma coagulation (H-APC) is a novel technique for the ablation of neoplastic Barrett Esophagus (BE), consisting in submucosal fluid injection and subsequent APC of visible BE. Aim of this study was to assess H-APC efficacy, safety and tolerability. Patients and methods. We prospectively included patients undergoing H-APC ablation at 4 Italian Hospitals from September 2022 to March 2024. Patients with BE C3M5 maximum extent, low- or high-grade dysplasia (LGD, HGD) or residual BE after endoscopic resection (ER) of visible lesions were included. Patients who had undergone previous ablative treatments were excluded. The primary endpoints were the complete eradication of intestinal metaplasia (CE-IM) and dysplasia (CE-D). The secondary endpoints were safety in terms of major and minor adverse events (AEs) and tolerability, assessed using pain (0-10) and dysphagia (0-5) scores within 7 days post-ablation. (NCT05645679) Results. Among the 51 enrolled patients (mean C 0.43 cm (SD 0.72), mean M 2.20 cm (SD 1.09)) who completed the treatment (80 H-APC sessions), 45.1% (23/51) had prior ER of visible lesions . All patients achieved both CE-IM and CE-D (51/51), requiring a mean of 1.51 (SD 0.83) sessions. Only one case of fever and absolute dysphagia was observed, 1/51 (1,96%) AEs. Regarding tolerability, mean pain score was 1.3 (SD 1.99) while mean dysphagia score was 1.28 (SD 0.56). Conclusions. The H-APC technique showed promising results in terms of effectiveness and safety with a good tolerability in achieving initial CE-IM and CE-D in a selected population of BE patients.